Disentangling the Influence of Socioeconomic Risks on Children's Early Self-Control - Terry Ng-Knight; Ingrid Schoon (Journal of Personality, 2017)
[Objective:] Previous studies have shown that individual differences in self-control emerge early in childhood and predict a range of important outcomes throughout childhood and adulthood. There is, however, less knowledge about the social origins of self-control, including the mechanisms by which early socioeconomic adversity may lead to lower levels of self-control. This study aimed to extend understanding of the link between socioeconomic adversity and self-control by (a) testing which individual aspects of socioeconomic risk uniquely predict lower self-control; (b) testing whether objective socioeconomic risk operates independently of, or via, subjective parental stress; and (c) examining the interplay of socioeconomic risk factors and individual differences in children's temperament as predictors of early self-control. [Method:] Data were from a UK population birth cohort of 18,552 children born in 2000 and 2001. [Results:] Multiple individual socioeconomic risk factors have independent associations with children's self-control, including low parental education, income, and occupational class; insecure housing tenure; and younger parenthood. Results point to independent additive effects of exposure to objective and subjective risk. There was evidence of mothers' subjective stress partially mediating objective socioeconomic risks but only weak evidence of hypothesized interaction effects between temperament and socioeconomic risk. [Conclusions:] Results were consistent with additive risk and bioecological perspectives.
Keywords: 330; Self-control; self-regulation; effortful control; socioeconomic risk; temperament